Flower Constancy of Bumblebees – The Case of Onobrychis pindicola (Fabaceae) Pollinators - Kozuharova, Ekaterina (Journal of Apicultural Science, 2018)
Pollination in high mountain habitats is an important ecosystem service in climate change conditions. The aim of this study was to use pollen load analysis to assess flower constancy and foraging choices of bumblebees foraging on a high-mountain endemic plant. The flower constancy to the foraging source was very high - over half of the bumblebees had pure Onobrychis-type pollen loads. In the mixed pollen loads we found one to seven pollen types other than Onobrychis-type and the functional flower morphology was different from the flag type. Some were gullet while others were dish/bowl functional morphology type. Thus the theory/belief that once discovering the flag blossom as a foraging resource bumblebees tended to visit other plants with such functional morphology was rejected. An abundance of plants did not determine food choice. We could not trace an obvious pattern of the bumblebees’ preference to functional blossom morphology but they were attracted to dish-bowl blossoms.